PARTICIPATORY SEARCHING FOR WISDOM HERITAGE OF MAECHAEM COMMUNITY IN CHIANG MAI PROVINCE FOR PROMOTING SUSTAINABLE TOURISM - Suvitcha Sritan, สุวิชชา ศรีถาน; Preeda Chaiya, ปรีดา ไชยา (Dusit Thani College Journal, 2018)
This study aims to investigate local wisdom heritage as participatory searching for tourism identity of MaeChaem Community. It also promotes sustainable tourism for the community by collecting data from fieldwork consisting of different sampling groups of the total 30 participants, such as community leaders, entrepreneurs of accommodation, restaurant, souvenir, monks and local scholars. The purposive sampling was used to select the participants from the following selected communities - Moo 4, Moo 5, and Moo 6 and Tambon Thapa. The instrument used for collecting data was comprised of 4 types; namely, 1) structured interview, 2) non - structured interview, 3) focus group, and 4) participatory observation. This study uses a descriptive technique to analyze the data. The findings indicate that the potential wisdom heritage for promoting sustainable tourism in Mae Chaem Community of Moo 4, Moo 5, and Moo 6 and Tambon ThaPa can be described as 1) wooden houses 2) Pha Sine Teen Jok 3) maechaem hairpin 4) soybean fermented 5) Ka – Nom tong Yong 6) Crisp rice or KawKiabWow 7) crab sauce 8) Ka – nom Wong 9) Stuffed Dough Pyramid 10) JunLaKaThin 11) Than Salakaput 12) Hing Fire Pra Chao 13) Lanna New Year, and 14) local dialects respectively.